Leech Saliva Extract Enhances Incisional Skin Wound Healing in Rats by Improving Neovascularisation and Tissue Regeneration - Ünal, Kübranur; Khusainov , Nurmukhamad; Erol, Mehmet Emre; Doruk, Mert; Dayanır, Duygu (Iraqi Journal of Science, 2025)
Medical leech therapy has been used for centuries due to its therapeutic effects. This therapy is mainly due to two main mechanisms: sucking and removing blood by leeches and secretion of leech saliva containing bioactive substances. This study investigated the effects of leech saliva extract (LSE) and medical leech therapy (MLT) on wound healing in rats with an incisional skin-wound model. The rats were divided into three groups: the control group (group I), the medical leech therapy group (group II), and the leech saliva extract group (group III). The wound healing process was observed and photographed morphologically on days zero and seven. After seven days, the rats were euthanised for detailed histological and biochemical examination. The histopathological findings revealed that group III indicated an accelerated healing process compared to other groups. In Group III, significant improvements in epithelial regeneration, granulation tissue thickness, fibroblast proliferation, neovascularisation, and reduced inflammation were observed. Vascular Endothelial Growth Factor (VEGF) (+) cell percentages were highest in Group III (75.60 ± 0.67), followed by Group II (67.00 ± 1.15), both significantly higher than the control group (46.16 ± 1.01) (p = 0.001). LSE demonstrates superior wound healing effects, likely by promoting epithelial and granulation tissue development and enhancing VEGF-driven neovascularisation. These findings underscore LSE's potential as a therapeutic agent for improving skin wound healing, with effects similar to or greater than medicinal leech therapy.